Temporal genetic structuring of a specialist parasitoid, Lysiphlebus hirticornis Mackauer (Hymenoptera: Braconidae) attacking a specialist aphid on tansy - Nyabuga, Franklin N. (My University, 2010)
In insect species characterized by inbreeding, limited dispersal, and a metapopulation structure, high genetic differentiation and reduced genetic diversity within local populations are expected. Using the model system Lysiphlebus hirticornis Mackauer, a specialist parasitoid of the tansy aphid, Metopeurum fuscoviride Stroyan (Hemiptera: Aphididae), we examined within-site temporal population dynamics and genetics, including molecular variation at the tansy plant level. Aphid-parasitoid dynamics were surveyed and parasitoids sampled from 72 tansy plants at 11 sites in and around Jena, Germany, over one growing season. Thereafter, parasitoid samples were genotyped at 11 polymorphic microsatellite loci. Colonization, extinction, and recolonization events occurred during the season. Allele numbers and identities were highly variable over time. When samples from all sites were pooled, allele number over all loci showed a decreasing trend with time. At the level of sites, temporal changes in genetic diversity were more variable. Analysis of molecular variance revealed that samples at the plant level explained the highest variance compared to at site level. We conclude that the genetic structuring of this insect is very fine grained (i.e. at the tansy plant level) and the temporal genetic diversity is explained by a combination of extinction and recolonization events, as well as inbreeding.
Keywords: alleles; diversity; gene flow; insects; metapopulation; Metopeurum fuscoviride; microsatellites; population dynamics; spatial genetics; Tanacetum vulgare